Analysis of the Effect of Load Equalization On Neutral Current at the TP0067 Distribution Substation of PT PLN (Persero) ULP Tanjung Pandan - Bella Rosmaida S; Hamdani Hamdani; Siti Anisah (Jurnal Info Sains : Informatika dan Sains, 2026)
Transformer load balancing is a mandatory maintenance activity that is regularly conducted to ensure the optimal performance of distribution systems. This activity serves as an essential effort to minimize neutral current, which contributes to power losses resulting from unbalanced loading conditions in distribution transformers. The load balancing process was carried out at Distribution Substation TP0067, with a capacity of 100 kVA, located within the operational area of ​​PT PLN (Persero) ULP Tanjung Pandan. The procedure commenced with load measurements on each feeder and phase, followed by detailed calculations of the phase load distribution. Based on the analysis results, the phases requiring load transfer to achieve balance were identified. Following the implementation of the load redistribution plan, it is expected that the neutral current will be significantly reduced, thereby reducing power losses and enhancing the overall efficiency and reliability of the distribution system.